2010
DOI: 10.3892/mmr.2010.351
|View full text |Cite
|
Sign up to set email alerts
|

Inflammatory stress promotes lipid accumulation in the aorta and liver of SR-A/CD36 double knock-out mice

Abstract: Abstract. Macrophage scavenger receptors (Srs), particularly type a Sr (Sr-a) and cd36, have been implicated in binding and internalizing modified forms of low-density lipoprotein (ldl) through a mechanism not regulated by cellular cholesterol content, resulting in cholesterol accumulation and foam cell formation. To test the impact of the absence of these receptors on lipid-mediated injuries in aortas or livers under inflammatory stress, C57BL/6 mice with knocked out SR-A and CD36 (SR DKO) were administered a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2012
2012
2014
2014

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 16 publications
(20 reference statements)
0
3
0
Order By: Relevance
“…Also, it may play a role in lipid exchange and transport throughout the body, as well as in reverse cholesterol transport from peripheral cells to the liver (Duchateau et al 2000). CD 36 is implicated in the binding and internalization of oxidized low-density lipoprotein (Ox-LDL) (Liu et al 2010). It is involved in cholesterol uptake in monocytes and macrophages (Anwar et al 2011) and contributes to cholesterol efflux in hepatic cells (Truong et al 2010).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Also, it may play a role in lipid exchange and transport throughout the body, as well as in reverse cholesterol transport from peripheral cells to the liver (Duchateau et al 2000). CD 36 is implicated in the binding and internalization of oxidized low-density lipoprotein (Ox-LDL) (Liu et al 2010). It is involved in cholesterol uptake in monocytes and macrophages (Anwar et al 2011) and contributes to cholesterol efflux in hepatic cells (Truong et al 2010).…”
Section: Resultsmentioning
confidence: 99%
“…Variants in this gene have been shown to be associated with increased HDL cholesterol levels (Liu et al 2010). In addition, variants in the gene are also associated with malaria resistance (Aitman et al 2000; Sirugo et al 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Human CD36 is expressed at very high levels in various cells and tissues of the body, including platelets, monocytes/macrophages, and microvascular endothelial cells, plays important roles in atherosclerosis, inflammation, thrombosis and angiogenesis [4,6,7,30,31,32], and is upregulated in human monocytes following statin administration [33]. Studies of Cd36¯/Cd36¯ knockout mice have shown that CD36 -deficiency protects against Western-type diet related cardiac dysfunction [34,35,36] and contributes to a reduction in fatty acid oxidation by muscle mitochondria [11,37]. Human clinical studies have also examined CD36 polymorphisms associated with enhanced atherosclerotic cardiovascular diseases [38,39], type II diabetes [9], oral fat perception, fat preference and obesity in African-Americans [40] and protection from malaria [41,42].…”
Section: Introductionmentioning
confidence: 99%